2022
DOI: 10.3389/fonc.2022.763926
|View full text |Cite
|
Sign up to set email alerts
|

Interest of the Addition of Taxanes to Standard Treatment in First-Line Advanced HER2 Positive Gastroesophageal Adenocarcinoma in Selective Patients

Abstract: BackgroundStudies have reported a beneficial role of the addition of trastuzumab to platin-5-FU based chemotherapy in first-line advanced HER2 positive gastroesophageal adenocarcinoma (GEA). However, the effect of taxanes combined with platin-5FU + trastuzumab (PFT) is understudied.MethodsWe performed a retrospective cohort study to evaluate the interest of taxanes among HER2-positive advanced GEA patients treated with PFT. We enrolled HER2-positive advanced GEA patients who underwent treatment between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…As an alternative to CPS, PFS and OS have been utilized to predict survival outcomes in gastric cancer (GC) through methods like Kaplan-Meier analysis and Cox proportional hazards models (4)(5)(6)(7)(8). Among these studies, Ozveren et al (6) identified an association between the inflammatory prognostic index (IPS) score (derived from C-reactive protein (CRP), neutrophil-tolymphocyte ratio (NLR), and serum albumin) and the risk of disease progression, highlighting the potential utility of clinical laboratory tests in predicting tumor response.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to CPS, PFS and OS have been utilized to predict survival outcomes in gastric cancer (GC) through methods like Kaplan-Meier analysis and Cox proportional hazards models (4)(5)(6)(7)(8). Among these studies, Ozveren et al (6) identified an association between the inflammatory prognostic index (IPS) score (derived from C-reactive protein (CRP), neutrophil-tolymphocyte ratio (NLR), and serum albumin) and the risk of disease progression, highlighting the potential utility of clinical laboratory tests in predicting tumor response.…”
Section: Introductionmentioning
confidence: 99%